Penerapan Undang-Undang No 8 Tahun 2010 Tentang Pencegahan Dan Pemberantasan Tindak Pidana Pencucian Uang (TPPU) Terhadap Penegakan Hukum Pidana Pencucian Uang (Money Laundering) Terhadap Tindak Pidana Kehutanan (Illegal Logging) - Dewi Ervina Suryani (Universitas Islam Sumatera Utara, 2020)
Money Laundering is a double crime that is continued crimes that frequently occur in Indonesia. This is indicated by the form of illegal money laundering as a crime that is a follow-up crime, while the main crime or crime of origin is known as predicate offense or core crime or there are countries that formulate it as unlawful activity, namely predicate crimes that generate money which are then carried out in the money laundering process (Money Laundering). As for one form of money laundering crime (Money Laundering), namely forestry crimes which are considered as predicate of crimes in the legal system as referred to in Law Number 8 of 2010 concerning the Prevention and Eradication of Money Laundering, of course it provides a legal basis for the law enforcement officers to carry out investigations and investigations as well as pursuing various suspicious transactions from financial institutions in order to seek cash flows that will eventually lead to intellectual actors holding funds for illegal logging activities. Although there are legal instruments that contain provisions of laws and regulations in the field of forestry and the environment, namely the Law Number 18 of 2013 concerning Prevention and Eradication of Forest Destruction and the Law Number 32 of 2009 concerning Environmental Protection and Management. However, in practice, the law enforcement has not been able to embrace the conception of understanding that in trapping perpetrators using the principle approach, it is suspected or should be suspected of having committed the crime of money laundering. What is being done now is to arrest the illegal logging actors who carry out